Development of grapes and wine-making industry of Moldova on the basis of modern achievements of science and innovations - Boris Gaina; Svetlana Fedorchukova; Galina Kobirman (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 11th Edition, 2020)
The wine-growing and wine-making complex of Moldova has come a long way: from metal-intensive technical equipment from unalloyed steels to modern European equipment from stainless, food-grade material. All new vineyard plantings are created from planting of certified material of our own production or acquired in Italy, France and Germany. At the present stage, vineyard plantations in Moldova are 80% occupied by classic European varieties. The rest - are local indigenous varieties. All technological processes in primary winemaking are based on modern biotechnology achievements and innovations: enzymes for clarifying wort, yeast for fermentation and bacteria to reduce acidity in red wines. The well-known preservative - sulfur dioxide is replaced with inert gases (nitrogen, carbon dioxide) and the use of low temperatures. Table wines are exported mainly to Romania, the Czech Republic, Germany, Poland, China, the United States and Canada. All the achievements of viticulture and winemaking in Moldova are based on the latest scientific and technological progress, developed and implemented in the Republic of Moldova by scientists from the Academy of Sciences of Moldova, universities, as well as specialists from the National Office of Grapes and Wine.
Keywords: Q13; 330; grape-wine-making complex; grape-based secondary products; European grape varieties; localindigenous varieties; wine market